Enhancing Heat Recovery Steam Generator Integrity: A Fitness-For-Service Approach using ASME FFS-1/API 579 for Remaining Life Assessment - Danang Priambada; Felixtianus Eko Wismo Winarto; Benidiktus Tulung Prayoga; Nur Rokhman; Nia Fararid Askar; Diki Bima Prasetio (GLOBAL HEALTH SCIENCE GROUP, 2026)
Assessment of the remaining life of a Heat Recovery Steam Generator (HRSG) that has been in operation for 24 years is crucial to ensure operational reliability, with the ASME FFS-1/API 579 standard as the primary reference. Analyze the material condition and assess the remaining life of HRSG Unit 2 based on the ASME FFS-1/API 579 standard. Data were collected through Non-Destructive Testing (UTM, LPT, MPT, UFD), visual inspection, borescope examination, and in-situ metallurgical tests to obtain microstructure and hardness profiles. The analysis was conducted by comparing inspection results with design specifications, evaluating microstructural changes, assessing hardness degradation, calculating remaining wall thickness, and performing fitness-for-service assessment according to ASME FFS-1/API 579. No significant cracks were found, but there was material thinning of up to 16.6% in some areas. The material condition is still good and meets design standards. The estimated remaining operational life is 10–15 years. HRSG Unit 2 is declared safe and reliable to operate. The ASME-based assessment method has been proven effective for estimating the remaining life and supporting a risk-based maintenance strategy.